2013
DOI: 10.1590/0103-6440201301992
|View full text |Cite
|
Sign up to set email alerts
|

Ex-vivo Effect of Intracanal Medications Based on Ozone and Calcium Hydroxide in Root Canals Contaminated with Enterococcus faecalis

Abstract: This ex vivo study evaluated the antibacterial effect of intracanal medications in root canals contaminated with Enterococcus faecalis. Fifty single-rooted human teeth were contaminated with E. faecalis (ATCC 29212) and incubated at 37°C for 21 days. The specimens were randomly divided into 5 groups according to the intracanal medication used: OZ-PG: ozonized propylene glycol; CH/CPMC: calcium hydroxide/camphorated paramonochlorophenol; OZ-PG/CH ozonized PG/CH; PC: positive control group (no medication); and N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
6
0
2
Order By: Relevance
“…Additionally, ozone has other advantages like such as improving wound healing, enhancing immune, no side effect, no-toxic, environmental friendly and high efficacy ( 12 ). A few studies have shown that ozone therapy is efficient in killing many kinds of microorganisms, such as S. aureus , Streptococci spp, Escherichia coli , Enterococcus faecalis , and P. aeruginosa ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, ozone has other advantages like such as improving wound healing, enhancing immune, no side effect, no-toxic, environmental friendly and high efficacy ( 12 ). A few studies have shown that ozone therapy is efficient in killing many kinds of microorganisms, such as S. aureus , Streptococci spp, Escherichia coli , Enterococcus faecalis , and P. aeruginosa ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another factor that may corroborate the results obtained in this study is the ephemeral ozone gas half-life. 24 The only techniques that have been tested so far and have showed a certain degree of effectiveness against LPS are (a) the use of calcium hydroxide as an intra-canal medication 12,25,26 as it hydrolyses lipid A and changes it into chains of fatty acid and nontoxic sugars, 27 and (b) the application of laser Nd:YAG. 9 The results obtained in this study reinforce the importance of instrumentation in addition to any disinfection protocol, 11,28,29 especially with regard to bacterial LPS that strongly adheres to the dentinal wall 6 and makes it necessary to use endodontic instruments for its removal.…”
Section: Discussionmentioning
confidence: 99%
“…Nekoliko metoda, kao što su korištenje raznih tehnika instrumentacije kanala (3), tehnike irigacije antimikrobnim otopinama (4) i intrakanalnih medikamenata (5), opisane su kako bi se postigla učinkovita intrakanalna dezinfekcija.…”
Section: Uvodunclassified